Antibiotic prescribing patterns at outpatient in Nanyuki Teaching and Referral Hospital, Laikipia County, Kenya - Kubai, Edna K.; Mokaya, Daniel; Gachohi, John (International Journal Of Community Medicine And Public Health, 2026)
Background: Antibiotics are the most commonly and often imprudently used therapeutics globally. The study of use of antibiotic is vital, as irrational use is a global public health threat. Very few studies are done on the out-patient prescribing patterns of antibiotic in Kenya. This study aimed to evaluate the antibiotic prescription patterns in the outpatient department in Nanyuki Teaching and Referral Hospital in Laikipia. Methods: We adopted a point prevalence study using the out-patient global PPS tool. Important variables had data represented in frequency tables and graphs. Chi-square determined the association between categorical variables and t-test for continuous variables. Confidentiality of data will be maintained throughout the study and STATA was used for analysis. Results: The point prevalence of antimicrobial use was (29.1%) patients who were receiving at least one antimicrobial agent at the time of the survey. Penicillins were the most commonly prescribed class (41.5%) followed by cephalosporins (21.6%). By age group, children had the highest proportion of prescriptions at 40.4%. Most common diagnostic indication was community acquired infection 89.5% that had least one antimicrobial while the highest infection is respiratory infections, at 26.3% of the cases, followed by gastrointestinal infections 19.8%. Cultures were rarely performed before initiating therapy, accounting for 1.8% only. Only 11.7%, of prescriptions were guided by existing local protocols. Conclusions: This study recommends strengthening antimicrobial stewardship (AMS) committees to routinely review prescribing trends, alongside expanding diagnostic services as culture and sensitivity facilities to support evidence-based antibiotic use. Additionally, improve the utilization of guidelines in treatment.